A Contrario Detection of H.264 Video Double Compression - Li, Yanhao; Gardella, Marina; Bammey, Quentin; Nikoukhah, Tina; Morel, Jean-Michel; Colom, Miguel; von Gioi, Rafael Grompone (2023 IEEE International Conference on Image Processing (ICIP), 2023)
Video manipulation detection plays a vital role in modern multimedia forensics. In particular, double compression detection provides significant clues leading to the video edition history and hinting at potential malevolent manipulation. While such an analysis is well-understood on images, the research on this subject remains lacking in videos and existing methods are not yet able to reliably detect double-compressed videos. This work presents a novel method for identifying double compression in H.264 codec videos. Our technique exploits the periodicity of frame residuals caused by fixed Group of Pictures in the initial compression, and employs an a contrario framework to minimize and control false detections. The proposed method can reliably detect double compression in videos. It does not require threshold tuning, thus enabling automatic detection. The code is available at https://github.com/li-yanhao/gop_detection.